Democratic trajectories in Africa : unravelling the impact of foreign aid - Resnick, Danielle, 1980-; Van de Walle, Nicolas, 1957-; World Institute for Development Economics Research (2013)
This volume examines how foreign aid has influenced democratic transitions and consolidation in sub-Saharan Africa.
"A study prepared by the United Nations University World Institute for Development Economics Research (UNU-WIDER)."
Includes bibliographic references and index.
Keywords: Economic development -- Africa, Sub-Saharan.; Economic assistance -- Africa, Sub-Saharan.; Democracy -- Africa, Sub-Saharan.; Africa, Sub-Saharan -- Economic conditions; Africa, Sub-Saharan -- Politics and government